Determinação do perfil dos erros de prescrição de medicamentos em um hospital universitário - Neri, Eugenie Desiree Rabelo (2004)
The cycle of the application of medication in hospital is very complex, being its first step: prescribing, recognized as a key-factor in medication errors. In Brazil, little is known about the determining factors and safety in the prescribing process. Based on a systemic error approach, an exploratory study was carried through in the Medical Care Unit of a University Hospital, determining the prevalence rate of errors in clinically significant prescribing (PRECSP), and the rate of safety in the prescribing process (RSPP). In this study, 474 medication orders were analyzed in June 2003, totalizing 3.460 items with medications (IWM). 31% of the medication orders referred to patients aged 60 or more and 72,15% were written by hand, with reference to legal and institutional criteria, key information aimed to guarantee and effective medication was missing in 75,30% of the medication, and abbreviations were used in 98,40% of the IWM, which being more evident among medications prescribed by physicians in the second year at residency (R2) (p<0,001). Medication prescribed by physicians in first year at residency (R1) showed a major rate of errors (12,70%; p=0,003). Clinically significant identified errors (CSE) (n=1012) were distributed in 395 medication orders and 78,10% of which pertaining to cardiovascular medication as a main therapeutic class. In the medication writing process, 75,40% (n=763) of the CSE were identified, the majority of the errors found were related to the omission of one or more items of patient identification (27,52%; n=210) and ambiguous or confused medication orders: 27,52% (n=210). Among the errors in the decision making process, the most common specific ones were potentially significant medication interactions (60,25%; n= 150), unidentified medication to patient (8,43%; n= 21) and overdose (6,83%; n=17). The major average of CSE was identified in the medical care unit (3,42+2,09; p=0,001) and the major rate of medication orders with CSE of which elaborated by RL (85,50%; p=0,011). Among the identified CSE, 98,42% (n=996) were potential and 7,8% (n= 79) were classified as potentially fatal or severe. The interventions were performed by pharmacists in 100% of the CSE identified, 88,66% of which were accepted by the physician. In the end, the PRECSP was estimated (29,25%) and the RSPP (70,75%), indicating the urgent need for the review of the prescribing process and the reevaluation of the educational strategies adopted by the physicians of the institution. Therefore, the findings showed prioritizing groups for the implement of strategies aimed to the reduction of CSE. As it comes out, the identification of prescribing errors, the rate of prevalence of clinically significant prescribing errors and the rate of the prescribing process safety constitute the first step in order to reduce the error rate associated with each system. However, in order to establish a more accurate systemic error prevention process in hospital settings, the responsibility for the safety of the patient must be seen collectively.